Real-world evaluation of nivolumab in patients with non-nasopharyngeal recurrent or metastatic head and neck cancer: a retrospective multi-center study by the Turkish Oncology Group (TOG) - Akyildiz, Arif; Guven, Deniz Can; Koksal, Baris; Karaoglan, Beliz Bahar; Kivrak, Derya; Ismayilov, Rashad; Aksoy, Sercan (Springer, 2024)
Objectives Head and neck cancers (HNCs) represent a significant global health concern due to high morbidity and mortality rates. Despite therapeutic advances, the prognosis for advanced or recurrent cases remains challenging. Nivolumab obtained approval for recurrent or metastatic HNC based on the Phase III CheckMate 141 trial. This study aimed to evaluate the real-world outcomes of nivolumab in patients with non-nasopharyngeal HNC. Design In this multicenter retrospective study, we analyzed 124 patients with recurrent or metastatic non-nasopharyngeal HNC who received nivolumab in the second-line setting and beyond. Data were collected from 20 different cancer centers across Turkey. The effectiveness and safety of the treatment and survival outcomes were evaluated. Results Nivolumab exhibited favorable clinical responses, yielding an objective response rate of 29.9% and a disease control rate of 55.7%. Safety assessments revealed a generally well-tolerated profile, with no instances of treatment discontinuation or mortality due to side effects. Survival analysis disclosed a median overall survival (OS) of 11.8 (95% CI 8.4-15.2) months. Multivariate analysis revealed that ECOG-PS >= 1 (HR: 1.64, p = 0.045), laryngeal location (HR: 0.531, p = 0.024), and neutrophil-to-lymphocyte ratio > 3.5 (HR: 1.97, p = 0.007) were independent predictors of OS. Conclusions Nivolumab is an effective and safe treatment option for patients with recurrent or metastatic non-nasopharyngeal HNC in real-world settings. Further studies are needed on factors affecting response to treatment and survival outcomes.
Keywords: Head and neck cancer; Nivolumab